Ibrutinib combined with rituximab and high-dose methotrexate in newly diagnosed primary CNS diffuse large B-cell lymphoma: a pilot study with long-term follow-up - Guo, Yixian; Shan, Yongzhi; Piao, Yueshan; Chang, Xiaoli; Zou, Dongmei; Ma, Qiang; Wei, Yukui; Xu, Geng; Wang, Yaming; Wang, Dandan; Teng, Lianghong; Wu, Chunxue; et al. (Frontiers in Oncology, 2025)
Key pointIRM appears promising and well tolerated as first-line therapy for newly diagnosed PCNS DLBCL in a small pilot cohort; these hypothesis-generating results require confirmation in larger prospective studies.BackgroundPrimary diffuse large B-cell lymphoma of the central nervous system (PCNS DLBCL) is a rare, aggressive lymphoma with rising incidence in elderly patients. Bruton tyrosine kinase (BTK) inhibitors show promise in recurrent/refractory cases, warranting exploration in newly diagnosed disease.MethodsThis single-center pilot study evaluated the safety/efficacy of ibrutinib, rituximab, and high-dose methotrexate (IRM) in nine newly diagnosed PCNS DLBCL patients (2018–2019). Treatment included 4 cycles of IRM induction, consolidation (HSCT or 2 additional IRM cycles), and maintenance therapy (ibrutinib/lenalidomide).ResultsAfter induction, overall response rate (ORR) was 100% (complete response [CR]: 77.8%, partial response [PR]: 22.2%). Post-consolidation, CR increased to 88.9%. At a median follow-up of 77.6 months, 5-year overall survival (OS) and progression-free survival (PFS) rates were both 77.8%, with 8 patients in sustained CR and one progression. No treatment-related deaths occurred; grade ≥3 adverse events were rare (2 neutropenia, 2 anemia, 1 gastrointestinal bleeding).ConclusionIn this small pilot cohort, IRM showed promising activity and tolerability as first-line therapy for PCNS DLBCL. These descriptive findings warrant confirmation in larger prospective trials (#ChiCTR1900027811).